Factor XIII deficiency in south of Tunisia. Issue 6 (September 2017) - Maaloul, Ines; Medhaffer, Moez; Louhichi, Nacim; Krichen, Imen; Alibi, Sofien; Kmiha, Sana; Aloulou, Hajer; Fakhfakh, Faiza; Elloumi, Moez; Kallel, Choumous; Hachicha, Mongia
Abstract : N/A: Factor XIII deficiency is a rare autosomal recessive disorder of hemostasis characterized by a plasmatic factor XIII level less than 1% in homozygote and bleeding as of the youth. The aim of the study is to describe the clinical features and the outcome of the patients and to determine molecular characteristics. A retrospective study, was conducted on seven patients with factor XIII deficiency in the department of hematology and pediatrics, Hedi Chaker Hospital, Sfax, Tunisia during the period of 14 years (2001–2014). The activity of factor XIII in plasma of the patients was less than 1%. Seven patients from five unrelated families were recorded( four men and three women). Median age at diagnosis was 3.5 years. All patients had consanguineous parents. Six patients presented umbilical bleeding and only three patients had intracranial bleeding. Other bleeding features were seen, including skin and mucosal bleeding, muscular hematoma, and splenic rupture. Recurrent abortions were observed in one patient. The standard screening tests were normal. Genetic analysis identified two mutations interesting the subunit A of factor XIII. All patients received transfusion of fresh frozen plasma monthly. One patient was died because of intracranial hemorrhage. Factor XIII deficiency is a rare bleeding disorder which frequently increases in areas with high consanguinity. In our study, we identified a founder mutation. The prognosis of the disorder is related to hemorrhagic complications especially to life-threatening intracranial bleeding. Prophylaxis consists of factor XIII concentrate or recombinant factor XIII. If these are unavailable, fresh frozen plasma may be used.